2019
DOI: 10.1080/10413200.2019.1630864
|View full text |Cite|
|
Sign up to set email alerts
|

A Mixed Methods Evaluation of a Pressure Training Intervention to Develop Resilience in Female Basketball Players

Abstract: Resilience has gradually gained attention in sport psychology. However, there remains a lack of knowledge on how this psychological characteristic can be developed. The aim of the present study was to evaluate the effectiveness of a pressure training intervention for resilience. In order to develop resilient qualities, the central feature of this intervention was the regular exposure to increased pressure during daily practice. This intervention was set up as a quasi-experimental switching replications design,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…Higher scores on the 'resilient characteristics' subscale indicated greater team resilience, whereas higher scores on the 'vulnerabilities under pressure' subscale suggested lower team resilience. Previous research has demonstrated evidence for the reliability and validity of data derived from this measure (Decroos et al, 2017;Gorgulu et al, 2018;Kegelaers et al, 2020). In the current study, Cronbach's alpha was .90 for resilient characteristics and .86 for vulnerabilities under pressure.…”
Section: Study Measuressupporting
confidence: 47%
“…Higher scores on the 'resilient characteristics' subscale indicated greater team resilience, whereas higher scores on the 'vulnerabilities under pressure' subscale suggested lower team resilience. Previous research has demonstrated evidence for the reliability and validity of data derived from this measure (Decroos et al, 2017;Gorgulu et al, 2018;Kegelaers et al, 2020). In the current study, Cronbach's alpha was .90 for resilient characteristics and .86 for vulnerabilities under pressure.…”
Section: Study Measuressupporting
confidence: 47%
“…Assessment and formulation principles from CBT and REBT, which aim to secure quantitative/qualitative/situational information on “who-what-where-when” shows promise. Psychometrics used as part of mixed-method, longitudinal designs have already shown promise in evaluating resilience (see Kegelaers et al, 2019 ; Chandler et al, 2020 ). Qualitative evidence in extant literature rates highly and has provided insight into the dynamic process of resilience across various sport samples and contexts (see Fletcher and Sarkar, 2012 ; Brown et al, 2015 , 2020 ; Morgan et al, 2015 , 2019 ; Timm et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, this study's findings can advance the trend in the literature toward more holistic PT interventions. Early studies focused on the effect of pressure in controlled experimental conditions (e.g., Oudejans & Pijpers, 2010), but recent studies have incorporated elements such as workshops and debriefs that supplement pressurized drills and better represent how practitioners may conduct PT in applied practice (e.g., Kegelaers et al, 2021;van Rens et al, 2021). Still, research has largely remained "practitioner-evacuated" (Ivarsson & Andersen, 2016).…”
Section: Delivery Of Pressure Training 21mentioning
confidence: 99%
“…Exploring delivery is especially pertinent now because of the recent increase in applied PT intervention studies. With the involvement of coaches, researchers have conducted PT in teams' training sessions for basketball (Kegelaers et al, 2021), cricket (van Rens et al, 2021, and soccer (Kent et al, 2021). Effective delivery is necessary for accurate evaluation of interventions.…”
mentioning
confidence: 99%